Cervidae antlers exploited to manufacture prehistoric tools and hunting implements as a reliable source of ancient DNA - Tejero, José-Miguel; Cheronet, Olivia; Gelabert, Pere; Zagorc, Brina; Álvarez-Fernández, Esteban; Arias, Pablo; Averbouh, Aline; Bar-Oz, Guy; Barzilai, Omry; Belfer-Cohen, Anna; Bosch, Marjolein D; Brück, Florian; et al. (Heliyon, 2024)
Antler is one of the primary animal raw materials exploited for technical purposes by the hunter-gatherer groups of the Eurasian Upper Palaeolithic (UP) all over the ecological range of deers, and beyond. It was exhaustively employed to produce one of the most critical tools for the survival of the UP societies: hunting weapons. However, antler implements can be made from diverse deer taxa, with different ecological requirements and ethological behaviours. Identifying the antler's origin at a taxonomic level is thus essential in improving our knowledge of humans' functional, practical and symbolic choices, as well as the human-animal interface during Prehistoric times. Nevertheless, palaeogenetics analyses have focused mainly on bone and teeth, with genetic studies of antler generally focused on modern deer conservation. Here we present the results of the first whole mitochondrial genome ancient DNA (aDNA) analysis by means of in-solution hybridisation capture of antlers from pre-Holocene archaeological contexts. We analysed a set of 50 Palaeolithic and Neolithic (c. 34-8ka) antler and osseous objects from South-Western Europe, Central Europe, South-Western Asia and the Caucasus. We successfully obtained aDNA, allowing us to identify the exploited taxa and demonstrate the archaeological relevance of those finds. Moreover, as most of the antlers were sampled using a minimally-invasive method, further analyses (morphometric, technical, genetic, radiometric and more) remain possible on these objects.
Keywords: Osseous tools; Ancient DNA; Upper palaeolithic; Hunting implements; Antler